Therapeutic resources used by traditional communities of the Brazilian Amazon: a scoping review - Altair De Farias; Fabíola de Carvalho; Franciane Farias; Joseir Cristino; Alicia Patrine dos Santos; Vinícius Machado; Sediel Ambrosio; Wuelton Monteiro; Jacqueline Sachett (Rural and Remote Health, 2024)
Introduction: The traditional communities of the Brazilian Amazon possess significant knowledge regarding the huge therapeutic arsenal available from natural sources that can be used to care for their health problems. This study aimed to identify, map and synthesize the scientific evidence on the use of traditional medicine as a therapeutic resource when used by traditional communities of the Brazilian Amazon. Methods: This is a scoping review, which is a method used to map the main concepts of a research area, the available evidence and its sources. It is developed in five steps: (1) identification of the research question; (2) identification of relevant studies; (3) selection of studies; (4) data analysis; and (5) grouping, synthesis and presentation of data. Results: Medicinal plants, vertebrates and invertebrates, among other medicinal products, are elements that are widely used by traditional populations. Plant stems, bark, leaves, flowers, fruits, seeds, roots, tubers and even the whole plant are prepared in various forms, such as teas, infusions, smoke for rituals, baths, macerations, oils, ointments, concoctions, dressings, incenses and exfoliants, among others. The main structures and forms used from animals are lards, fats, viscera, horns, cocoons, nests, feathers and beaks of birds, eggs and roes. These therapeutic practices are often carried out using endogenous, wild and domesticated natural resources present in the biodiverse environments of traditional populations. They involve magical-religious beliefs to treat all types of illnesses, including cultural syndromes that affect children, young people, adults and the elderly. Conclusion: This scoping review has an important role to disseminate and expand the discussion of traditional medicine practices, inviting readers - whether they are health professionals, community members, managers or decision-makers - to a continuing debate using an intercultural dialogue necessary to improve approaches. From this perspective, it is essential to consider the comprehensive legal and legal framework that guides the public policies of national health systems.